Health for all: A fundamental goal of public health in our region - Binns, Colin; Lee, M. (SAGE Publications Inc., 2015)
Since its foundation 30 years ago, the mission of the Asia-Pacific Academic Consortium for Public Health has been promoting "health for all" through public health. "Health for all" became the theme of Walter Patrick's public health career and inspired his contribution to APACPH. However, the universality of health care is now under threat, more from economists and politicians than public health workers. Health for all remains a continuing challenge for all public health workers in our region. Progress is being made toward this goal as life expectancy in the Western Pacific has increased from 64 to 78 in the past 3 decades. Prof Walter Patrick was strong public health advocate, and this review was written as a tribute to good friend and inspiring colleague who believed in, and worked for "health for all."